Pengembangan Mobile Learning â€œDetektif Siputâ€ Kelas X SMK - Rindiani, Rindiani; Hasanah, Fitria Nur (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The purpose of this study was to develop and determine the feasibility of learning media, in the form of mobile learning with the name "Snail Detective" for class X students majoring in Computer and Network Engineering at Dian Indonesia Vocational High School Sidoarjo. The development model used in this study is the ADDIE model which consists of the analysis, design, development, implementation, and evaluation stages. The subjects in this study were students of class X majoring in Computer and Networking Engineering. The research instrument used is in the form of a questionnaire. The data obtained will then be analyzed using the likert scale. â€œDetective Snailâ€ mobile learning was validated by media experts, material experts, and tested on groups with a limited scale. Based on the results of the development, it was found that the development of "Snail Detective" mobile learning in class X SMK Dian Indonesia Sidoarjo was declared very feasible as a learning support tool. The validation results from media experts get a score percentage of 94% with a very decent category, the results of material expert validation get a score percentage of 87% with a very decent category and trials to students get an average score percentage of 91.2% with a very decent category . So it is concluded that the â€œSnail Detectiveâ€ mobile learning is very feasible to use and can be implemented for the learning process.